O011 Why joint location matters in the pathogenesis of rheumatoid arthritis - Frank Bertoncelj, M; Karouzakis, E; Masterson, T; Kolling, C; Distler, O; Ospelt, C (Annals of the rheumatic diseases, 2018)
IntroductionInflammatory arthritis, such as rheumatoid arthritis (RA) and spondyloarthropaties, follows a characteristic anatomical pattern of joint involvement. We suggest that the local cell types, systemic triggers and site-specific exogenous factors that activate these local cells synergistically contribute to the site-specific occurrence of arthritis.ObjectivesTo explore the role of the local stromal cells – synovial fibroblasts (SF), in defining the joint-specific synovial biology, relevant for RA.MethodsWe studied transcriptomes, epigenomes and functions of hand, shoulder and knee SF from patients with RA or osteoarthritis and from knees of nonarthritic subjects with arthralgia by using RNA-sequencing (Illumina HiSeq 2000, n=21), histone ChIP-sequencing (Illumina HiSeq 2500, n=7), Infinium HumanMethylation450 BeadChip (n=12) and in vitro assays for proliferation, adhesion and chemotaxis. We silenced the long noncoding RNA HOTTIP in hand SF using LNA GapmeR, followed by RNA-sequencing (n=2), protein-protein interaction analysis (STRING) and qPCR confirmation of the HOTTIP target genes. Paraffin embedded RA synovial tissues (n=48) from different joints were scored by the Krenn synovitis score for leukocyte infiltration, synovial lining and density of synovial stroma.ResultsThe transcriptomes, the global DNA methylation patterns and the histone marks, which mark the actively transcribed DNA regions (H3K27ac) and enhancers (H3K4me1), defined the joint-specific origin of SF. Hand SF showed prominent proliferative, chemotactic and matrix-degrading properties. Hand synovial tissues exhibited increased density of stroma and leukocyte infiltration. The homeobox (HOX) genes that regulate hand embryogenesis (HOXA13, HOTTIP) were the top differentially expressed genes with hand-specific expression in SF. This hand-specific expression pattern coincided with the specific enrichment of the activating histone marks H3K4me3 and H3K27ac and the absence of repressive H3K27me3 and DNA methylation at the HOTTIP and HOXA13 promoters in hand SF. In contrast, shoulder and knee SF displayed abundant H3K27me3 and DNA methylation, but scarce H3K4me3 and H3K27ac at the HOTTIP and HOXA13 promoters. Silencing of HOTTIP in hand SF altered the expression of 447 mRNA genes with a log ratio >|2| (FDR<0.05). The HOTTIP regulated genes were strongly enriched in the mitotic cell cycle protein interaction network (n=48 genes, p=3.29×10–7). Several of these genes were confirmed as downregulated by HOTTIP silencing in a larger cohort of hand SF (n=6, p<0.05). Besides, the basal expression of the enriched cell cycle genes, including CDC27 and TADA3, significantly correlated with the basal HOTTIP expression in hand SF (n=21).ConclusionsThe lncRNA HOTTIP, which is specifically expressed in hands via epigenetic mechanisms regulates the mitotic cell cycle genes. This might imprint hand SF with an enhanced proliferative potential and might promote the synovial hyperplasia in hand joints, thereby increasing the severity of hand RA.AcknowledgementsIRR-IRF, Promedica, Georg und Berta Schwyzer Winiker Stiftung, CABMM.Disclosure of interestM. Frank Bertoncelj Grant/research support from: IRR-IRF, Promedica, Georg und Berta Schwyzer Winiker Stiftung, CABMM, E. Karouzakis: None declared, T. Masterson: None declared, C. Kolling: None declared, O. Distler: None declared, C. Ospelt Grant/research support from: IRR-IRF, Promedica, Georg und Berta Schwyzer Winiker Stiftung, CABMM